PEMBERANTASAN KORUPSI DALAM DIMENSI RADICAL HUMANIST DAN RADICAL STRUCTURALIST: MENENGOK (PULA) PERAN AKUNTAN(SI) FORENSIK - Achdiar Redy Setiawan (Universitas Trunojoyo Madura, 2012)
As a nation state, Indonesia faces great challenges to deal with corruption. While all nation members discussing about how to combat corruption, it ends up in discourse and rhetoric words. Corruption is still a huge problem that has not been solved yet until now. We have to go far away to find out the root of this terrible problem. Then, optimistic view need to be put in mind that Indonesia would be corruption free in the future. In line with those positive thinking spirit, this paper try to build strategy to minimize corruption phenomenon. I, borrow the Burrel Morgan paradigm, suggest two kinds of strategies: consciousness (radical humanist) and structural changes (radical structuralist). Furthermore, the role of forensic accounting to contribute in combating corruption is also elaborated here. Hopefully, it could give a basic action plan to all stakeholders to work together toward “Indonesia: clean without corruption.